Societal views on substance use disorders : exploring the hidden stigma attached to drug and alcohol use disorders in Iceland - Arnrún Bergljótardóttir 1996- (2022)
Substance use disorders, specifically drug and alcohol use disorders, affect all levels of society, and raising awareness of this mental illness is important to overcome stigma and prejudice. This current study set out to explore the views of Icelanders on substance use disorders. These views were analyzed in connection to age, educational level, knowledge on substance use disorders, and personal experience of the disorders. A total of 409 participants with different backgrounds responded to an online survey; 59.7% of the participants were females and 40.3% were males. The survey questions focused on the etiology of substance use disorders, views on individuals living with the disorders, and personal experience of discrimination against these individuals. Analysis of variance (ANOVA) and independent samples t-test were used to interpret the study outcome. The results of the study displayed that age, education, and personal experience of substance use disorders did not affect the Icelanders’ views on the disorders. Knowledge on substance use disorders did, however, have a positive influence on these views. These results indicate that providing education to the public on the etiology of substance use disorders could help lessen the prejudice towards individuals with the disorders. Keywords: substance use disorders, prejudice, views, Icelanders, etiology, discrimination Fíknisjúkdómar snerta allar hliðar samfélagsins og fræðsla um þessi andlegu veikindi er mikilvæg til að draga úr fáfræði og fordómum. Markmið þessarar rannsóknar var að kanna viðhorf Íslendinga til fíknisjúkdóma. Þessi viðhorf voru borin saman við aldur, menntunarstig, eigin þekkingu á fíknisjúkdómum og persónulega reynslu af sjúkdómnum til að kanna hvort tengsl væru á milli breytanna. Samtals 409 þátttakendur með mismunandi bakgrunn tóku þátt í rafrænni könnun; 59.7% voru konur og 40.3% voru karlar. Könnunin innihélt spurningar sem tengdust þekkingu á fíknisjúkdómum, viðhorfi til einstaklinga með fíknisjúkdóma, og persónulegri reynslu af mismunun ...